KEEFEKTIFAN TEKNIK JIGSAW TERHADAP PEMBELAJARAN MEMBACA TEKS CERPEN SISWA KELAS VII SMP NEGERI 1 V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - -, Asriliana - (Pendidikan Bahasa Indonesia, 2014)
This study aims to : ( I ) describe the process of learning to read a short story textcomprehension class VII - 5 SMP Negeri 1 V Koto Kampung Dalam Kabupaten Padang PariamanDistrict before the jigsaw technique is applied, ( 2) describe the process oflearning to read a shortstory text comprehension class VII - 5 SMP Negeri I V Koto Kampung Dalam Kabupaten PadangPariaman District after the jigsaw technique is applied, and ( 3 ) determine the effectiveness of thetechnique is applied before and after the learning jigsaw text reading comprehension short storiesseventh grade students of SMP Negeri I V Koto Kampung Dalam Kabupaten Padang PariamanDistrict.This research is a quantitative study . The method used in this study is experimental withpre - experimental design . The study population was a class VII student enrolled in the schoolyear 2013/2014 , and the sample is Vll.5 grader who amounted to 25 people . The samplingtechnique applied is purposive sampling . The instrument used in this study was a test , a test thatis applied is the essay test .Based on the results of data analysis and discussion, it can be concluded , results of thisstudy as follows. ( I ) the ability to read text stories VII.5 grade students ofSMP Negeri I V KotoKampung Dalam in the jigsaw technique was applied prior to the qualification is more thanadequate with an average value of 70.16 . ( 2 ) the ability to read text stories VII.5 grade studentsof SMP Negeri I V Koto Kampung Dalam in the jigsaw technique was applied after qualifyingwell at all with an average value of 89.6 . Through hypothesis testing using t-test measurementsobtained t of 6.94 and 2.060 ttable at P 0.05 . Comparison between tcount with ttabel show that tcount greater than t table . This means that the hypothesis ( HI ) , there are significanteffectiveness of the differences before and after the jigsaw technique is applied to the ability toread text stories VII.5 grade students of SMP Negeri I V Koto Kampung Dalam, the hypothesis(H l ) is accepted .